Skeletal muscle pathology in endurance athletes with acquired training intolerance. Issue 6 (23rd November 2004) - Grobler, L A; Collins, M; Lambert, M I; Sinclair-Smith, C; Derman, W; St Clair Gibson, A; Noakes, T D
Abstract : Background: It is well established that prolonged, exhaustive endurance exercise is capable of inducing skeletal muscle damage and temporary impairment of muscle function. Although skeletal muscle has a remarkable capacity for repair and adaptation, this may be limited, ultimately resulting in an accumulation of chronic skeletal muscle pathology. Case studies have alluded to an association between long term, high volume endurance training and racing, acquired training intolerance, and chronic skeletal muscle pathology. Objective: To systematically compare the skeletal muscle structural and ultrastructural status of endurance athletes with acquired training intolerance (ATI group) with asymptomatic endurance athletes matched for age and years of endurance training (CON group). Methods: Histological and electron microscopic analyses were carried out on a biopsy sample of the vastus lateralis from 18 ATI and 17 CON endurance athletes. The presence of structural and ultrastructural disruptions was compared between the two groups of athletes. Results: Significantly more athletes in the ATI group than in the CON group presented with fibre size variation (15 v 6; p = 0.006), internal nuclei (9 v 2; p = 0.03), and z disc streaming (6 v 0; p = 0.02). Conclusions: There is an association between increased skeletal muscle disruptions and acquired training intolerance in endurance athletes. Further studies are required to determine the nature of this association and the possible mechanisms involved.